Cytoprotective Antioxidant, Anti-Inflammatory, and Antifibrotic Impact of Celery Seed Oil and Manuka Honey Against Cyclophosphamide-Induced Cystitis in Rabbits. (17th March 2022) - Mousa, Ayman M.; Allemailem, Khaled S.; Alhumaydhi, Fahad A.; Alrumaihi, Faris; Almatroudi, Ahmad; Aljasir, Mohammad; Alwashmi, Ameen S. S.; Al Rugaie, Osamah; Soliman, Khaled E. A.; Aljohani, Abdullah S. M.; Al Abdulmonem, Waleed; Ahmed, Ahmed A.; et al.
Abstract : Patients treated with cyclophosphamide (CP) usually suffer from severe hemorrhagic cystitis (HC). Our previous study exhibited that mesna + celery cotherapy partially ameliorated HC. Therefore, there is a substantial need to seek alternative regimens to get complete protection against CP-induced HC. The current study investigated the effects of mesna + celery seed oil (MCSO) or mesna + manuka honey (MMH) cotherapy against CP-induced HC in adult male rabbits. The forty rabbits were divided into four equal groups and treated for three weeks. The control group (G1) received distilled water and the second group (G2) received CP (50 mg/kg/week). The third group (G3) received CP + MCSO (CPMCSO regimen), and the fourth group (G4) received CP + MMH (CPMMH regimen). The urinary bladder (UB) specimens were processed to evaluate UB changes through histopathological, immunohistochemical, ultrastructural, and biochemical investigations. In G2, CP provoked HC features (urothelial necrosis, ulceration, and sloughing), UB fibrosis, and TNF- α immunoexpression. Besides, CP reduced the activity of antioxidant enzymes (GPx1, SOD3, and CAT) and elevated the serum levels of NF- κ B, TNF- α, IL-1B, and IL-6 cytokines in G2 rabbits. In contrast, the CPMMH regimen caused significant increments of UB protection against HC in G4 rabbits compared to the partial protection by the CPMCSO regimen in G3. Therefore, our study indicated for the first time that the novel CPMMH regimen resulted in complete UB protection against CP-induced HC via combined antioxidant, anti-inflammatory, and antifibrotic properties.